Three-photon excited fluorescence imaging in neuroscience: From principles to applications - Xiao, Yujie; Deng, Peng; Zhao, Yaoguang; Yang, Shasha; Li, Bo (Frontiers in Neuroscience, 2023)
The development of three-photon microscopy (3PM) has greatly expanded the capability of imaging deep within biological tissues, enabling neuroscientists to visualize the structure and activity of neuronal populations with greater depth than two-photon imaging. In this review, we outline the history and physical principles of 3PM technology. We cover the current techniques for improving the performance of 3PM. Furthermore, we summarize the imaging applications of 3PM for various brain regions and species. Finally, we discuss the future of 3PM applications for neuroscience.